An Avenue of Royal Palms at the Trinidad Country Club - (:unkn) unknown (My University, 2010)
The postcard shows a line of stately palms outside the Trinidad Country Club, Maraval.
Colour: Coloured (print); Style: Portrait; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Palms--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Maraval; Trinidad Country Club